2011
DOI: 10.1063/1.3667198
|View full text |Cite
|
Sign up to set email alerts
|

Molecular binding energies from partition density functional theory

Abstract: Approximate molecular calculations via standard Kohn-Sham density functional theory are exactly reproduced by performing self-consistent calculations on isolated fragments via partition density functional theory [P. Elliott, K. Burke, M. H. Cohen, and A. Wasserman, Phys. Rev. A 82, 024501 (2010)]. We illustrate this with the binding curves of small diatomic molecules. We find that partition energies are in all cases qualitatively similar and numerically close to actual binding energies. We discuss qualitative … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
64
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 57 publications
(65 citation statements)
references
References 39 publications
0
64
1
Order By: Relevance
“…When the exact partition energy is used, either via iterative inversions [NWW11] or through use of the exact T S [n], any approximate Qfunctions such as Equation 23, satisfying the sum-rule:…”
Section: In Practice: Converging To Self-consistencymentioning
confidence: 99%
“…When the exact partition energy is used, either via iterative inversions [NWW11] or through use of the exact T S [n], any approximate Qfunctions such as Equation 23, satisfying the sum-rule:…”
Section: In Practice: Converging To Self-consistencymentioning
confidence: 99%
“…In particular, WFT-in-DFT embedding utilizes the theoretical framework of DFT embedding to enable the WFT description of a given subsystem in the effective potential that is created by the remaining electronic density of the system. [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] We recently introduced a simple, projection-based method for performing accurate WFT-in-DFT embedding calculations 30 that avoids the need for a numerically challenging optimized effective potential (OEP) calculation 24,25,[31][32][33][34] via the introduction of a level-shift operator. It was shown that this method enables the accurate calculation of WFT-in-DFT subsystem correlation energies, as well as many-body expansions (MBEs) of the total WFT correlation energy.…”
Section: Introductionmentioning
confidence: 99%
“…It is also shown in Figure 5 that the most gain in charge in the donor molecule occurs in the region of the σ * O−H orbital. The bonding region is conveniently described by the one-dimensional plot along the bonding x-axis: as in the cases of the diatomic molecules mentioned above, 3,6 the partition potential is somewhat diminished in the bonding region, decreasing in the O1→H5 direction, which we associate with the electron flux due to the n O → σ * O−H charge transfer.…”
Section: 2832mentioning
confidence: 99%
“…The partition potential can be related to functional derivatives of E p ; however, because its exact form is not known, iterative methods for optimizing v p have been developed. 2,3,6 These involve writing v p as linear combinations of basis functions and directly optimizing the coefficients so that the the sum of fragment densities matches a precalcuated supermolecular density, n m when projected onto the basis functions of v p .…”
Section: Theoretical Backgroundmentioning
confidence: 99%